Quantification of chemical mutagenesis in diploid human fibroblasts: Induction of azaguanine-resistant mutants by N-methyl- N′-nitro- N-nitrosoguanidine - Jacobs, Lois; Demars, Robert (Mutation Research/Environmental Mutagenesis and Related Subjects, 1978)
The toxic and mutagenic effects of N-methyl- N′-nitro- N-nitrosoguanidine (MNNG) on cultured diploid human fibroblasts were studied. When 10 5 cells per 60 mm dish were exposed to MNNG for 4 h in Ham's medium F10 containing 0.02 M HEPES buffer at pH 6.8, MNNG concentrations of less than 1 × 10 −6 resulted in cell survivals near 100%, while the average survival was less than one percent at concentrations greater than 5 × 10 −6 M. After treatment with MNNG, cells were subjected to selection using optimal conditions for the detection of diploid human fibroblasts that are resistant to the guanine-analogs AG and TG because they contain altered or deficient HPRT. The induced mutant frequency was maximized by allowing a 5 to 7 day post-treatment interval for the expression of the mutant phenotype and by replating the cells at the beginning of selection at a population density of less than 450 cells per cm 2. Careful attention was given to counting statistically adequate numbers of mutants and to accurately determining cell survival and replating cloning efficiencies. Independent dose-response experiments gave induced mutant frequencies as high as 7.0 × 10 −4 to 8.8 × 10 −4 mutants per viable cell at about 5% survival, compared to a spontaneous mutation rate of 3.7 × 10 −6 to 7.2 × 10 −6 mutants per cell generation. The AG r mutants observed after treatment with MNNG were phenotypically stable and closely resembled prototype AG r cultures derived from humans who have inherited mutant X-chromosomal alleles for HPRT.